The Effect of Information and Communication Technology (ICT) on Inclusive Green Growth (IGG) in Indonesia - Alfiani Farida; Syafruddin Karimi; Febriandi Prima Putra (International Journal of Economics Development Research (IJEDR), 2023)
The sustainable development paradigm gives rise to the concept of inclusive green growth. It focuses not only on economic growth but also on social inclusion and environmental sustainability. This study aims to measure inclusive green growth at the provincial level in Indonesia in 2013-2021 and investigate the impact of ICT on it. The composite index method is used in this study to measure inclusive green growth. Furthermore, this research uses panel data regression to examine the impact of ICT on inclusive green growth. The results show that Indonesia's inclusive green growth achievements are still in the moderate category. The provinces in the Eastern Indonesia region tend to have lower achievements in social dimensions. However, in the Western Indonesia region, the provinces tend to have lower achievements in environmental dimensions. The regression analysis showed that utilization of mobile phones and the internet had a significant positive effect on inclusive green growth. On the other hand, computer and fixed telephone ownership had an adverse effect on it. Equitable distribution of ICT development, especially in Eastern Indonesia and rural areas, should be continuously encouraged through investment in ICT and its supporting infrastructure.